Effect Of Biomass Dosage on Biosorption Malachite Green Using Immobilized Langsat Shell (Lansium Domesticum Corr) - Niswatul Inayah; Desy Kurniawati (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
Malachite green dye waste is one of the wastes that is genotoxic and carcinogenic to humans. Biosorption is an effective process for the removal and recovery of Malachite green dye waste from aqueous solutions. In this study, the biomass used was a langsat shell which had been immobilized with sodium silicate. The obtained biosorbents were characterized using Fourier Transform Infra-Red (FTIR). In this research, we determine the effect of biomass dosage on biosorption Malachite green using the column method. The results showed that the optimum conditions for absorption occurred at biomass dosage 2 gram . The maximum biosorption efficiency of 96,85%